The effect of triathlon on urinary excretion of enzymes and proteins - Yaguchi, H.; Ishigooka, M.; Hayami, S.; Kobayashi, T.; Kubota, Y.; Nakada, T.; Mitobe, K. (International Urology and Nephrology, 1998)
In order to investigate the effect of triathlon and renal function of normal subjects, we evaluated the excretion of urinary enzymes and proteins before and after triathlon. From 6 subjects samples were obtained 24 hours after the first urine collection. We performed quantification of urinary total protein, beta2-microglobulin (beta2-M), N-acetyl-beta-D-glucosaminidase activity (NAG), and concentration of urinary creatinine from each participant. There was a significant increase in urinary total protein excretion immediately after triathlon (p<0.01). The urinary beta2-M and NAG excretions after triathlon were higher than the initial values. Post-exercise proteinuria in one subject persisted until the next morning, whereas the increased excretion of urinary beta2-M and NAG returned to the pre-exercise level at least 24 hours after triathlon. It appears to be reasonable to presume that glomerular damage may persist in some subjects who do heavy exercise.